Outage Probability of Dual-Hop Relay System with Interference and Feedback Delay in Satellite M2M Networks. (22nd October 2013) - Lin, Yuan; He, Yuanzhi; Huang, Qinfei; Yin, Hao; Feng, Shaodong
Abstract : The machine-to-machine (M2M) communication enables information exchange between machine devices, which can be carried out without or with minimal human interaction. In this paper, we analyse the outage probability of satellite M2M communication system using amplify-and-forward (AF) and decode-and-forward (DF) relaying schemes. Both the channel feedback delay and multiple interferers at the relay and destination are taken into consideration. The channels of the two hops are modeled as Rayleigh and Rician, respectively. The closed-form outage probability expressions for both AF fixed-gain and DF relaying system are obtained, and the validness of our analytical results are verified by the Monte Carlo simulations. It is shown that the channel delay affects the outage probability performance more significantly compared with the interferences. It is also worthy to note that the DF relaying system provides better performance than AF fixed-gain relaying system, especially when the feedback delay is short. Moreover, it can be found that the performance gaps of the two relaying schemes become trivial as the feedback delay increases.